Pseudomonas fluorescens rates increase nitrate reductase activity and reduce shoot nitrate accumulation in hydroponic lettuce - Oliveira, Carlos Eduardo da Silva; Gato, Isabela Martins Bueno [UNESP]; Jalal, Arshad [UNESP]; Girardi, Vitória de Almeida Moreira [UNESP]; Oliveira, Júlia Revolti [UNESP]; Tamburi, Karen Vicentini [UNESP]; Caetano, Geovana Cunha [UNESP]; Oliveira, Rafaela Marega [UNESP]; Aguilar, Jailson Vieira [UNESP]; Camargos, Liliane Santos de [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Taylor & Francis, 2025)
Inoculation with Pseudomonas fluorescens has been widely used due to its growth promotion and potential influence on plant nitrogen (N) metabolism. The objective of this study was to estimate the rate of P. fluorescens that provides the greatest growth, chlorophyll, foliar nitrate reductase (NR) enzyme activity and the reduction of nitrate (NO3−) accumulation in hydroponic lettuce plants. The treatments consisted of different rates of P. fluorescens inoculant via the nutrient solution, with rates ranging from 0, 8, 16, 32 and 64 mL 100 L−1 of solution. Inoculating with P. fluorescens at a dosage ranging from 23 and 34 mL 100 L−1 of solution resulted in significantly greater fresh and dry mass for both the shoots and roots of the plants. Notably, at rates of 32 and 37 mL 100 L−1 of P. fluorescens, there was a 39% increase in N accumulation and a remarkable 192% increase in ammonium (NH4+) accumulation in the shoots. Simultaneously, there was a significant 65% reduction in NO3− accumulation in the shoots, and at the highest rate of P. fluorescens, the NR activity increased. In addition, it was observed an increasing in the concentration of chlorophyll a, chlorophyll b, carotenoids, total carbohydrates and total amino acids in the leaves by 43, 74, 50, 98 and 165% at rates of 35, 36, 37, 38 and 50 mL 100 L−1 of P. fluorescens. Inoculation of P. fluorescens at a rate of 35 mL 100 L−1 via nutrient solution in hydroponic lettuce cultivation provided increase of photosynthetic efficiency, N uptake, mass accumulation, shoot yield and a decrease in the accumulation of NO3− in the plant shoots.
Keywords: Amino acids content; carbohydrates content; growth promoting bacteria; Lactuca sativaL; nitrogen uptake; photosynthetic efficiency